A robust autonomous sliding-mode control of renewable DC microgrids for decentralized power sharing considering large-signal stability - Li, Xiangke (2023)
DC microgrids (MGs) are providing a pathway toward a zero-carbon-based future. The intermittent renewable energy sources (RESs) and non-linear constant power loads (CPLs) thrive in DC MGs, craving for effective coordinative control solutions to ensure the stability of DC MGs. In this paper, a robust autonomous sliding mode control (SMC) scheme is proposed for achieving a globally stable and decentralized power sharing operation of multiple dispatchable units (DUs) in CPL-integrated DC MGs. Firstly, by using the high-order finite-time observer (HOFTO) technique, the disturbances, such as the power coupling and parameter uncertainties between different DU-interfaced converters, are self-eliminated within a finite time without any output current sensor and communication link. Secondly, a decentralized control scheme synthesizing the robust SMC and droop control algorithm is proposed to achieve proportional power sharing among paralleled DUs and precise DC bus voltage regulation. The proposed control guarantees the global system's large-signal stability by ensuring the local stability of an individual converter, offering a simple yet effective stable coordinative solution. Finally, simulation and experimental results verify the effectiveness of the proposed strategy.